Proteome of granulosa cells lipid droplets reveals mechanisms regulating lipid metabolism at hierarchical and pre-hierarchical follicle in goose - Yuan, Xin; Zhang, Xi; Lin, Yueyue; Xie, Hengli; Wang, Zhujun; Hu, Xinyue; Hu, Shenqiang; Li, Liang; Liu, Hehe; He, Hua; Han, Chunchun; Gan, Xiang; et al. (Frontiers in Veterinary Science, 2025)
Avian hierarchical follicles are formed by selection and dominance of pre-hierarchical follicles, and lipid metabolism plays a pivotal role in this process. The amount of lipid in goose follicular granulosa cells increases with the increase of culture time, and the neutral lipid in the cells is stored in the form of lipid droplets (LDs). LD-associated proteins (LDAPs) collaborate with LDs to regulate intracellular lipid homeostasis, which subsequently influences avian follicle development. The mechanism by which LDAPs regulate lipid metabolism in goose granulosa cells at different developmental stages is unclear. Therefore, using BODIPY staining, we found that at five time points during in vitro culture, the LD content in hierarchical granulosa cells was significantly higher than that in pre-hierarchical granulosa cells in this study (p < 0.001). Next, we identified LDAPs in both hierarchical and pre-hierarchical granulosa cells, and screened out 1,180, 922, 907, 663, and 1,313 differentially expressed proteins (DEPs) at the respective time points. Subsequently, by performing Clusters of Orthologous Groups (COGs) classification on the DEPs, we identified a large number of proteins related to lipid transport and metabolism. Following this, the potential functions of these DEPs were investigated through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analysis. Finally, the important pathway of fatty acid degradation and the key protein ACSL3 were screened out using Short Time-series Expression Miner (STEM) and Protein–Protein Interaction (PPI) analysis methods. It is hypothesized that ACSL3 may potentially modulate lipid metabolism through the fatty acid degradation pathway, thereby contributing to the difference in lipid content between hierarchical and pre-hierarchical granulosa cells. These findings will provide a theoretical foundation for further studies on the role of LDs and LDAPs in avian follicle development.